FAKTOR-FAKTOR YANG MEMENGARUHI OPINI AUDIT MODIFIKASIAN GOING CONCERN - Tjong, Louvin Lesmana; Daryatno, Andreas Bambang (Universitas Multimedia Nusantara, 2024)
Abstract” The COVID-19 pandemic (2020-2022) had a significant impact on the hotel, restaurant, and tourism sectors, affecting the survival of many businesses. During this period, government-imposed restrictions on social movement led to the closure or bankruptcy of several companies. This research aims to provide empirical evidence regarding the influence of auditor quality, company growth, and company size on going concern modified audit opinions. The study focuses on companies within the hotel, restaurant, and tourism subsectors listed on the IDX between 2020 and 2022. Using purposive sampling, 72 data points were selected for analysis. Logistic regression analysis, performed with SPSS version 25, revealed that auditor quality, company growth, and company size had no significant effect on going concern modified audit opinions. This finding suggests that both Big Four and non-Big Four audit firms play an important, similar role in assessing and reporting on going concern issues. Auditors present an accurate view of a company's status, without being influenced by pandemic conditions. A decline in sales during the pandemic does not necessarily indicate financial distress, as management can still effectively manage assets to ensure business survival. This research serves as a reference for managers to make informed decisions during difficult times and helps investors and stakeholders carefully assess risks when considering investments or providing loans. Keywords: Auditor Quality; Company Growth; Company Size; Going Concern Modified Audit Opinions